Rapid improvement in soil health following the conversion of abandoned farm fields to annual or perennial agroecosystems - Chamberlain, Lucas A.; Aguayo, Teresa; Zerega, Nyree J. C.; Dybzinski, Ray; Egerton-Warburton, Louise M. (Frontiers in Sustainable Food Systems, 2022)
Incorporating perennial crops into agroecosystems has been shown to mitigate soil degradation and improve soil health by enhancing soil aggregation and soil organic carbon (SOC) accrual. However, our understanding of the ability and timeframe for perennial crop systems to build soil health within the context of conversion from abandoned crop land remains limited. Here, we examined changes in soil health in the first year following the conversion of an abandoned crop field into an agroecosystem planted with various treatments, including: novel perennial grain (intermediate wheatgrass, IWG; Thinopyrum intermedium), IWG/ alfalfa biculture, forage grass, tallgrass prairie, or annual wheat. We analyzed factors considered central to the concept of mitigating soil degradation to improve soil health (soil aggregation, aggregate organic carbon (OC), bulk SOC) and their soil biological and physicochemical correlates throughout the first growing season. Comparisons between treatments showed that both annual and perennial treatments rapidly and significantly improved soil health metrics including aggregation, aggregate stability, and OC levels compared to pre-conversion conditions. Such increases were positively correlated with the abundance of arbuscular mycorrhizal fungi (AMF hyphae, root colonization), labile SOC and microbial activity. Notably, IWG/ alfalfa biculture resulted in significantly higher levels of macroaggregate OC in comparison to other treatments, including tallgrass prairie, supporting the potential of perennial grasses to contribute to soil carbon gains. Overall, the conversion of this abandoned land to an agroecosystem produced rapid and substantial increases in soil health in the first year after planting.